Multilocus genotyping of a 'Candidatus Phytoplasma aurantifolia'‐related strain associated with cauliflower phyllody disease in China. (2nd March 2016) - Cai, H.; Wang, L.; Mu, W.; Wan, Q.; Wei, W.; Davis, R.E.; Chen, H.; Zhao, Y.
Abstract: A new cauliflower disease characterised by the formation of leaf‐like inflorescences and malformed flowers occurred in a seed production field located in Yunnan, a southwest province of China. Detection of phytoplasma‐characteristic 16S rRNA gene sequences in DNA samples from diseased plants linked the cauliflower disease to phytoplasmal infection. Results from phylogenetic and virtual restriction fragment length polymorphism analyses of the 16S rRNA gene sequence indicated that the cauliflower‐infecting agent is a ' Candidatus Phytoplasma aurantifolia'‐related strain and is a new member of the peanut witches'‐broom phytoplasma group, subgroup A (16SrII‐A). Multilocus genotyping showed close genetic relationship between this cauliflower phytoplasma and a broad host range phytoplasma lineage found only in East Asia thus far. Molecular markers present in the secY and rp loci distinguished this phytoplasma from other members of the subgroup 16SrII‐A.